THE SCENARIO IMPACT OF LOCAL CIGARETTE TAX TO GOVERNMENT’S FISCAL AND ECONOMIC - Muhammad Yusmal Nikho (Widyariset, 2011)
This research is addressed to improve the preparation of implementing local cigarette tax in January 2014. This research will discuss the impact of cigarette tax to the government’s fiscal and economic by applying several alternative scenarios of cigarette tax. Quantitative methodology is used to calculate its impact on the government’s fiscal and economic (using I-O analysis). The result showed that the application of the cigarette tax would reduce cigarette consumption and production, increase total government revenue from tobacco products, reduce the central government’s net revenue from the tobacco excise tax, increasing the total revenue and spen ding of provincial government significantly, reduce fiscal capacities inequality among provincial government, as well asincreasing output, income, and employment.